Pengaruh Eco-Efficiency dan Intellectual Capital terhadap Kinerja Keuangan Perusahaan Consumer Non-Clycicals yang Terdaftar di BEI Tahun 2022-2024. - Winia Agasy; Usnia Wati Keristin (Universitas Multi Data Palembang, 2026)
Discrepancies in previous research regarding the connection between Eco-Efficiency, intellectual capital, and financial performance highlight the need for additional study. This research aims to explore how Eco-Efficiency and intellectual capital affect the financial outcomes of companies in the non-clycical consumer sector listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. A quantitative methodology is utilized, relying on secondary data obtained from the IDX. The sample consists of 44 firms chosen through purposive sampling, with the data analyzed using multiple linear regression. The results indicate that Eco-Efficiency does not significantly impact financial performance, while intellectual capital has a notable partial effect. Overall, both Eco-Efficiency and intellectual capital significantly impact financial performance.